Seguir con el problema (de género): la subjetividad poshumana, melancolía y ficción distópica según Mariña Pérez Rei y María Reimóndez - Moszczyńska-Dürst, Katarzyna; Garrido González, Ana (Moderna Språk, 2024)
Posthuman feminism abandons the notion of representing a universal subject and questions the phallogocentric and humanist paradigm of the symbolic order. Subjectivity becomes ex-centric, nomadic, animalistic (both personal and communal). This, in turn, allows for the redefinition of certain interiorized narratives in relation to nature, gender, materiality and the body; those schools of thought focus on precarious and vulnerable lives, both human and non-human (Braidotti, 2022; Barad, 2007; Haraway, 2020; Segarra, 2022). Science fiction has become prominent in creating, rewriting and debating the theoretical and political positions mentioned above. Hence, the aim of this article is to analyse through the lenses of ecofeminism, posthumanism, memory, and mourning/melancholia processes three dystopian novels written by Galician women writers: M. Pérez Rei´s Canícula (2007) and M. Reimóndez’s Cobiza (2021) and Multitudes (2022). The article delves into the intricate interplay among melancholy, social transformation, and political engagement, as codified in the analysed dystopian narratives. Thus, we will question the extent to which the dystopian melancholic literature is rife with the peril of succumbing to immobility. We argue that despite their apparent detachment and seemingly apolitical stance, the mourning/melancholia dialectic inscribed in those novels fosters a political and ethical contemplation of vulnerable subjectivities/ communities and agency.